Carpal tunnel syndrome secondary to an accessory muscle: a patient with a variant of palmaris longus - Fontan, Francisco Rodriguez; Netscher, David T. (International Surgery Journal, 2025)
Carpal tunnel Syndrome (CTS) can be idiopathic or secondary to various factors such as trauma, anatomical variations, systemic conditions, or exertion. Diagnosing CTS typically relies on clinical evaluation, including history and physical examination. This case report details a 27-year-old female with juvenile rheumatoid arthritis (JRA) presenting with CTS likely due to rheumatoid arthritis-related flexor tendon synovitis. However, during surgery, an unexpected palmaris longus (PL) muscle variant was identified at the distal forearm as the primary cause of compression. The PL variant, which had not been detected preoperatively by MRI, was located proximal to the wrist crease and was excised during an extended open carpal tunnel release with flexor tendon synovectomy. This case underscores the importance of considering anatomical variations, such as accessory muscles, in CTS diagnosis and treatment. This is important, particularly in the patient seemingly unresponsive to the more common release operation that does not ordinarily enter the forearm. In this patient, serendipitously she had an extended incision on the premise of needing to perform a flexor tenosynovectomy. Surgeons should remain aware of these variations to prevent persistent symptoms and improve surgical outcomes in CTS management.